Economic evaluations in exploration - Wellmer, Friedrich-Wilhelm (Springer Berlin Heidelberg, 2008)
Now that we know how to calculate the revenues (the net smelter return) for a potential mine from the grades of a deposit to be evaluated (Chap. 7); how to determine the life-time of a mine (Chap. 8); and how to derive capital and operating costs from the capacity (Chap. 9), we have all the data required to carry out economic calculations.